Girl-Child Education: A Challenge for Sustainable Development in Nigeria - Atama, Grace C. (Richtmann Publishing, 2012)
Girl-child education is crucial for sustainable development. When you educate the woman, you educate anation. Children look up more to their mothers as role models than to their fathers and it is true thatwomen have primary influence on their children. Therefore, uneducated women are likely to bring uppoorly mannered or uneducated children. Communities that do not give adequate attention to educate thegirl-child are usually characterized with mass illiterates, ill equipped to deal with life situations aroundthem as their knowledge will be very limited thereby working against sustainable development. It is, anestablished fact that behind every successful man, there is a woman who should also have some attainedlevel of education. This paper therefore sees the girl-child education very important for attainingsustainable development. The paper begins with an introductory highlight, the concepts of the girl-child,and education were briefly discussed, the importance/benefit of girl-child education were examined. Thechallenges and strategies for improvement were forwarded and conclusion given.